2020
DOI: 10.1097/cad.0000000000000886
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 modulates cisplatin resistance of gastric cancer cells by inhibiting autophagy via the PI3K/Akt/mTOR pathway

Abstract: Resistance to cisplatin (DDP) remains a major obstacle in the control of gastric cancer (GC) progression. A previous study revealed that microRNA-21 (miR-21) contributes to DDP resistance in GC cells via the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) pathway. The aim of the current study was to explore the mechanisms underlying the cytoprotective function of miR-21. In this study, DDP-resistant GC cells were obtained by continuous exposure of human gastric adenocarcinoma cells to increasing concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Although the anti‐autophagic function of miR‐21 has been elaborated in the hypoxia/reoxygenation‐exposed cardiomyocytes, 28 and renal tubular epithelial cells during renal ischaemia‐reperfusion, 29 its involvement in the human cancer cells remains largely unknown. miR‐21 was recently proposed as an inhibitor of autophagy in gastric cancer and therefore to enhance drug resistance 30 . The present study emphasized the tumour‐promotive role of miR‐21 in NPC by suppressing the cell autophagy.…”
Section: Discussionsupporting
confidence: 52%
“…Although the anti‐autophagic function of miR‐21 has been elaborated in the hypoxia/reoxygenation‐exposed cardiomyocytes, 28 and renal tubular epithelial cells during renal ischaemia‐reperfusion, 29 its involvement in the human cancer cells remains largely unknown. miR‐21 was recently proposed as an inhibitor of autophagy in gastric cancer and therefore to enhance drug resistance 30 . The present study emphasized the tumour‐promotive role of miR‐21 in NPC by suppressing the cell autophagy.…”
Section: Discussionsupporting
confidence: 52%
“…Hsa_circ_0010882 also activates PI3K/ Akt signaling and promotes gastric cancer development 25 . Previous studies p‐PI3K can activate Akt to form p‐Akt, and then participate in the process of gastric cancer development and development 26‐30 . It was shown p‐PI3K and p‐Akt were reduced after Herceptin treatment in gastric cancer cells, and hsa_circ_0000520 overexpression could restrain p‐PI3K and p‐Akt level.…”
Section: Discussionmentioning
confidence: 91%
“…Tian et al (2018) have suggested that miR-361-5p negatively regulates the expression of FOXM1, which further causes an increase in the expression of p-AKT and mTOR, the inhibition of autophagy, and the enhanced sensitivity of gastric cancer cells to Docetaxel (DOC) in vitro. Gu et al (2020) have found that miR-21 overexpression can increase the phosphorylation of AKT and mTOR, inhibit autophagy, and induce DDP resistance. It has been further demonstrated that the knockdown of miR-21 can promote autophagy and then sensitize DDP-resistant gastric cancer cell lines to DDP (Gu et al, 2020).…”
Section: Regulatory Effects Of Mirnas On Autophagy-mediated Gastric Cmentioning
confidence: 99%
“…Gu et al (2020) have found that miR-21 overexpression can increase the phosphorylation of AKT and mTOR, inhibit autophagy, and induce DDP resistance. It has been further demonstrated that the knockdown of miR-21 can promote autophagy and then sensitize DDP-resistant gastric cancer cell lines to DDP (Gu et al, 2020).…”
Section: Regulatory Effects Of Mirnas On Autophagy-mediated Gastric Cmentioning
confidence: 99%